Daily concurrent chemoradiotherapy using retrograde superselective intra-arterial infusion for locally advanced squamous cell carcinoma of the mandibular gingiva. Issue 6 (November 2018) - Oguri, Senri; Mitsudo, Kenji; Iida, Masaki; Iwai, Toshinori; Koizumi, Toshiyuki; Hirota, Makoto; Kioi, Mitomu; Koike, Izumi; Hata, Masaharu; Tohnai, Iwai
Abstract: Objective: We previously reported that daily concurrent chemoradiotherapy using retrograde superselective intra-arterial infusion for locally advanced oral cancer provided good local control and overall survival rates. This study was performed to evaluate the therapeutic results of daily concurrent intra-arterial chemoradiotherapy for patients with locally advanced squamous cell carcinoma of the mandibular gingiva. Methods: Sixteen patients with T3, 4 mandibular gingiva cancer who refused surgery underwent definitive intra-arterial chemoradiotherapy between August 2006 and July 2014. Treatment consisted of concurrent chemoradiotherapy using retrograde superselective intra-arterial infusion (60 Gy, total dose; 60 mg/m2 for docetaxel and 150 mg/m2 for cisplatin). Results: Complete response of the primary site was obtained in 14 patients (87.5%). Five-year local control and survival rates were 73.4%and 81.3%, respectively. Grade 3 or 4 toxicities including mucositis and neutropenia were seen in 13 patients (81.3%) and 6 patients (37.5%), respectively. Grade 3 osteoradionecrosis occurred as a late adverse event in 1 patient (6.3%). Conclusions: Retrograde daily concurrent intra-arterial chemoradiotherapy for locally advanced carcinoma of the mandibular gingiva provided good local control and overall survival rates. This method can become one of the therapeutic options for patients with locally advanced carcinoma of the mandibular gingiva.